Influencing student motivation and teaching English as a foreing language through poems, games, stories and songs aiming an efective learning process - Monceau Pazmiño, Michelle (2008)
Traditional or rigid education has not delivered a good educational product. Students who learn through such methods do not achieve in high percentages the desired skills. It has been observed that those language-teaching realities must be changed and are beginning to change. Students are prone to develop writing skills and to learn grammar as formulas, also English as a second language is first produced as a literal translation of the first language of the students. An enticing learning environment can be achieved through different approaches such as games, songs and creative activities. If the mentioned playful activities are applied in teaching English as a second language, results will boost because students will be highly motivated, and will learn to talk and communicate amongst themselves without using 'formulas' or translation, rather in a natural way. This process is very similar to the first language acquisition.